Respon Pernapasan Anak dengan Pneumonia yang Mendapatkan Terapi Oksigen - Fredita Andriana Putri; Siti Arifah (Journal of Telenursing (JOTING), 2026)
This study aimed to describe the respiratory response in children with pneumonia receiving oxygen therapy. The research method used was a case study of two children, aged 9 and 11 years with pneumonia who received oxygen therapy. Changes in oxygen saturation (SpO₂) and respiratory rate (RR) were observed gradually before therapy, and 1 hour, 2 hours, and 4 hours after administration. The results showed that oxygen therapy improved the respiratory condition of both patients. In patients using nasal cannula (3 L/minute), SpO₂ increased from 93% to 97% within 1 hour and reached 98% at 4 hours, accompanied by a gradual decrease in RR. In patients using NRM (6 L/minute), SpO₂ increased from 89% to 96% within 1 hour and reached 97% at 4 hours, with a more rapid decrease in RR in the initial hours of therapy. In conclusion, there was respiratory improvement after oxygen therapy, with a more rapid response appearing in the early phase of NRM use.   Keywords: Nasal Cannula, Non-Rebreathing Mask, Pneumonia, Respiratory Response, Oxygen Therapy